The role of sensory diet in minimalization of food selectivity in children with autism spectrum - case study - Habik-Tatarowska, Natalia (Journal of Education, Health and Sport, 2019)
In the group of disorders in children with autism spectrum observed food selectivity. The article presents a case study of a therapeutic program applied to a child with food selectivity.A 5-year-old boy with a diagnosed autism spectrum was selected for the observation. The criterion for including the child in the observation was the diagnosed food selectivity and hypersensitivity of the touch system. For this purpose, a detailed interview with parents and medical consultations were made during which food selectivity due to metabolic disorders was excluded. The boy participated in a six-month therapy conducted once a week by the Sensory Integration method. The research was conducted from July to December 2018.The child was observed to minimize the degree of hypersensitivity of the tactile system after a period of 3 months of the sensory diet. After 6 months of treatment, a significant progress was observed in the widening of the boy's nutritional repertoire. Currently, the child eats most of the food without diversifying the food structure.In the child's case study analyzed, the effectiveness of Sensory Integration therapy applied in food selectivity was confirmed. The effectiveness of stimulation of Sensory Integration Therapy is an opportunity to improve the minimization of food choices in children with the autism spectrum.